PENGEMBANGAN MODEL PEMBELAJARAN LOMPAT JAUH GAYA JONGKOK MELALUI PERMAINAN LEVEL JUMP DAN GARIS TANGKAP PADA SISWA KELAS VII SMP NEGERI 1 TULIS KECAMATAN TULIS KABUPATEN BATANG TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study is to produce a product development model of learning style long jump squat in Physical Education Sport and Health through the game levels to jump and catch the lines of class VII students of SMP N 1 TULIS .This research is a development . The analysis procedure includes product development product that will be created , developed the initial product , expert validation and revision , testing and revision of small groups , large groups and test the final product . The data was collected using a questionnaire derived from expert evaluation , as well as using field observations obtained from the students . The data analysis technique used is descriptive percentages . From the existing research results it can be concluded that the model of learning and jump levels game fishing line can be used as a teaching model for students of class VII Penjasorkes SMP N 1 TULIS , because in reality the learning model contributes three aspects of cognitive , affective and psychomotor and more create a pleasant atmosphere so that students become motivated.